Coconut Carbon Sequestration Part 2 / Strategies for the Carbon Market & Simulating Potential Incomes for Coconut CDM Projects - O. Roupsard (International Coconut Community Journal, 2008)
The following article is a review of possible strategies of the coconut sector facing the carbon market, through the Clean Development Mechanism (CDM) of the Protocol of Kyoto, but also through Non-Kyoto (voluntary) initiatives. It sums up the conditions for certifying plantations, together with recent statistics of similar projects accepted by UNFCCC, which are currently displaying a rapid growth rate. It stresses the complexity of the CDM, but also the accessibility for coconut energy & afforestation + reforestation (A/R) projects, considering that coconut plantations do actually correspond to the definition of “forest”. Using recent scientific information on C cycle of coconut plantations and coconut oil, it proposes also a simulation of the expected potential profitability of coconut energetic and A/R projects. From the point of view of the farmer and of the oil mill, in absence of any CDM project (the reference here), the value-added comes mainly from local processing of the copra into coconut oil. When implementing a short-term A/R project (t-CER), the value-added by C fixation in the ecosystem would be ca. +15 to +19%, as compared to the copra and oil references. When implementing a long-term project (l-CER), the value-added would reach +40 to +52%. When implementing an energy-oil project solely, the value-added by C fixation in the coconut oil would be only +5% (this not including other benefits at national scale, however). When implementing a dual A/R + energy-oil project, the value-added by C fixation would be +19% for t-CER, and +45% for l-CER with respect to the copra and oil references. These results are just potential values given for example, suspected to vary much according to the actual conditions of coconut plantation productivity, management and also C market conditions. However, the simulation clearly supports every APCC initiative in this direction.